Polymorphisms in methylenetetrahydrofolate reductase gene and risk of non-Hodgkin lymphoma in a multi-ethnic population - Sujatha, S.; Gan, G.G.; Zain, S.M.; Haerian, B.S.; Bee, P.C.; Lian, L.H.; Chang, K.M.; Ong, T.C.; Mohamed, Z. (Nature Publishing Group, 2014)
An imbalance in folate metabolism can adversely affect DNA synthesis and methylation systems which can lead to susceptibility to non-Hodgkin lymphoma (NHL). Whether single nucleotide polymorphisms (SNPs) and their haplotypes in the methylenetetrahydrofolate reductase (MTHFR) are associated with NHL, remain inconclusive. We investigated the association between MTHFR C677T and A1298C SNPs and NHL risk in a population which is made up of Malay, Chinese and Indian ethnic subgroups. A total of 372 NHL patients and 722 controls were genotyped using the Sequenom MassARRAY platform. Our results of the pooled subjects failed to demonstrate significant association between the MTHFR C677T and A1298C SNPs with NHL and its subtypes. The results were in agreement with the previous meta-analyses. In the Indian ethnic subgroup however, single locus analysis of MTHFR A1298C appears to confer risk to NHL (Odds ratio (OR) 1.91, 95% confidence interval (95% CI) 1.22–3.00, P¼0.006). The risk is almost doubled in homozygous carrier of MTHFR 1298CC (OR 4.03, 95% CI 1.56–10.43, P¼0.004). Haplotype analysis revealed higher frequency of CC in the Indian NHL patients compared with controls (OR 1.86, 95% CI 1.18–2.93, P¼0.007). There is lack of evidence to suggest an association between MTHFR C677T and A1298C with the risk of NHL in the Malays and Chinese. In the Indians however, the MTHFR A1298C confers risk to NHL. This study suggests ethnicity modifies the relationship between polymorphisms in the folate-metabolizing gene and NHL.